Preoperative tranilast as adjunctive therapy to primary pterygium surgery with a 1-year follow-up - Almeida Junior,Gildásio C. (2015)
Purpose: To determine the efficacy of tranilast as an adjunctive therapy in conjunctival autograft. Methods: Twenty-nine patients were randomly allocated to the Tranilast Group (n=15) or the Control Group (n=14). The Tranilast Group received a subconjunctival injection of 0.5% tranilast 30 days prior to surgery. Conjunctival autograft was performed in both groups using fibrin sealant and 0.02% subconjunctival mitomycin C at the end of the surgery. After the resection of the pterygium, immunohistochemistry was performed with 100 cells to identify epithelial cells positive for transforming growth factor-β (TGF-β). Subjective symptoms were evaluated using a 5-point scale, and the recurrence rate was assessed. Results: Both groups showed improvements in their symptoms and similar clinical results. Compared with the Control Group, the Tranilast Group failed to show a decreased recurrence rate (p=0.59). However, the number of epithelial cells expressing TGF-β was lower in the Tranilast Group (5 cells; 95% CI: 2.56-13.15; Control Group, 16 cells, 95% CI: 11.53-24.76; p=0.01). Minimal but reversible complications, including glaucoma secondary to corticosteroids and granuloma, occurred during the study. Conclusion: Tranilast was effective in decreasing the number of pterygium epithelial cells expressing TGF-β.